PENERAPAN AI (CHATGPT) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA - Zesmita Zesmita; Ahmad Suryadi (Taksasila Edukasi Insani, 2025)
This study aims to identify the learning strategies of Civic Education (PPKn) at SMA Muhammadiyah 25 Pamulang and to explore the professionalism and criteria of students' abilities in the form of thinking competence. This research uses a descriptive qualitative method with a case study approach, conducted at SMA Muhammadiyah 25 Pamulang. Data collection techniques were carried out through observation, interviews, and documentation. The research subjects involved 1 Civic Education teacher and 3 students. The results of the study show that the implementation of ChatGPT in Civic Education learning has encouraged a shift from traditional learning models toward a more participatory and student-centered approach. Through this technology, teachers can present learning materials in a more exploratory way, while students are assisted in understanding abstract materials more simply. The use of ChatGPT has proven to be quite effective in improving students' comprehension, facilitating more active discussions, and fostering the development of critical thinking skills. ChatGPT offers advantages in terms of quick access to information and flexibility in adapting to students' needs. However, its success highly depends on the teacher's role as a facilitator. Nevertheless, the potential for using ChatGPT is significant if directed properly to enhance the quality of Civic Education learning.Keywords : AI, ChatGPT, Critical Thinking, Learning